Reactions to Misoprostol: A Case Report - Arsalan Salari; Aseme Pourrajabi; Samaneh Karami; Zahra Hamidi Madani (Clinical Medicine Insights: Case Reports, 2023)
Background: Most of abortions occur before the 13th week of pregnancy. Nowadays, non-surgical approaches for evacuation of uterine have been replaced with surgical ones due to the reduction in bleeding, fewer complications, ease of management, and cost-effectiveness. Misoprostol is a prostaglandin E1 analog that is used for labor induction. It is known as a safe drug with very few side effects. Case Presentation: A 29-year-old woman with the gestational age of 11 weeks and 6 days with a diagnosis of cystic hygroma introduced herself to the labor ward. At the time of hospitalization, the patient was conscious. The heart sounds were normal. A vaginal exam indicated no pathological findings. Totally, she received 1000 mg of Misoprostol. Approximately, 2 hours after the last placement of Misoprostol, the patient developed bending and mild cyanosis of fingers and showed tachycardia with a pulse rate of 140 beats/min. Her O 2 saturation decreased to 78%. At this time, the patient had a successful miscarriage. Echocardiography showed an ejection fraction of 55% and normal right ventricular size. The electrocardiogram showed sinus tachycardia. Therefore, she was sent to CCU with a possible diagnosis of embolism. The cardiologist administered a heparin drip of 5000-unit IV stat, and 1000 unit/h heparin and asked for a D-Dimer test. However, the laboratory reported that the patient’s blood sample was hemolyzed and they could only check her hemoglobin which was 4 g/dl. Immediately, the heparin drip was held and the patient received 3 packed cells. Her Hb was 6.5 g/dl. 12 hours later she showed tachycardia, and her O 2 saturation reduced to 70%. She lost her consciousness. Nearly 40 minutes later, she had cardiorespiratory arrest and CPR wasn’t successful and she died. Conclusions: In Conclusion, even a frequently used drug such as Misoprostol can cause life-threatening side effects, leading to emergent situations.